Drivers of sustainability and consumer well-being: an ethically-based examination of religious and cultural values - Minton, Elizabeth A. (Journal of business ethics, 2022)
Prior research has examined value antecedents to sustainable consumption, including religious or cultural values. We bridge together these usually separated bodies of literature to provide an ethically-based examination of both religious and cultural values in one model to understand what drives sustainable consumption as well as outcomes on consumer well-being. In doing so, we also fulfill calls for more research on socio-demographic antecedents to ethical consumption, particularly in the domain of sustainable consumption. We examine this relationship using data from the religiously and culturally diverse country of Singapore (n = 1503), collected from a door-to-door, representative sample utilizing numerous quality control techniques. Our path analysis and logical follow-up tests reveal that both religious and cultural values influence sustainable consumption, and then sustainable consumption positively influences consumer well-being. Implications are provided for consumer ethics, business' ethical practices, and belief congruence theory.